Praktik Penguasaan Tanah Oleh WNA Melalui Perjanjian Pinjam Nama (Nominee) dalam Sistem Hukum di Indonesia - Fini Annisa Sudhuri (CV Rewang Rencang, 2024)
Starting from the charm of beautiful Indonesian tourism, many foreigners not only invest but also own land that can be owned in Indonesia through a nominee loan agreement. This is certainly prohibited in the UUPA, where only Indonesian citizens can have property rights and control absolutely a land. The purpose of this study is to find out the practices, mechanisms, and impacts that occur due to the existence of a nominee loan agreement between foreigners and Indonesian citizens. This research is processed with a normative juridical approach method, namely by looking at law as a set of regulations/rules or doctrines that have a normative nature (law in book). The result of the discussion is that the practice of borrowing names (nominees) is still rampant until now, especially in tourism cities in Indonesia. The nominee loan agreement between a foreigner and an Indonesian citizen is considered to harm the UUPA and does not meet the legal requirements of the agreement, which causes the agreement to be null and void. Keywords: Property Rights, Nominee Agreement, Basic Agrarian Law